Estimation of coseismic surface displacement in the Aso-Caldera area caused by the 2016 Kumamoto Earthquake, with the Geomorphic Image Analysis using differential LiDAR DEM - SATO, Takumi; NISHIMURA, Tomohiro; MUKOYAMA, Sakae (Journal of the Japan society of photogrammetry and remote sensing, 2021)
After the main shock of 2016 Kumamoto Earthquake (Mj7.3), coseismic wide-area crustal deformation was observed around Aso region in Kumamoto Prefecture, Japan. In this study, multi-temporal LiDAR DEMs and Digital Geomorphic Image Matching method was applied to measure ground displacements of 1m scale in wide-area.As a result, seismic wide-area crustal deformation around caldera and displacements along a lot of surface ruptures of the earthquake faults were observed. Additionally, large lateral slides of the area of 1-2km diameter were observed in the flat caldera floor filled with unconsolidated sediment. Amount of displacements of these area were 1-4m.